2020
DOI: 10.1101/2020.12.18.423524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal omics in Syrian hamsters integrated with human data unravel complexity of moderate immune responses to SARS-CoV-2

Abstract: In COVID-19, the immune response largely determines disease severity and is key to therapeutic strategies. Cellular mechanisms contributing to inflammatory lung injury and tissue repair in SARS-CoV-2 infection, particularly endothelial cell involvement, remain ill-defined. We performed detailed spatiotemporal analyses of cellular and molecular processes in SARS-CoV-2 infected Syrian hamsters. Comparison of hamster single-cell sequencing and proteomics with data sets from COVID-19 patients demonstrated inter-sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Hoagland and colleagues researchers assessed the lungs of SARS-CoV-2 infected hamsters for host immune gene regulation and found a prominent upregulation of IL-6, TNF, and IL-1beta 49 consistent with our PCR results. In another study single cell sequencing analysis revealed a prominent T cell response including upregulation of IFN-gamma and IL-2 50 , two markers we also noted to be highly expressed in the lungs. Importantly, the qRT-PCR analysis we reported in our present study is in agreement with these other studies thereby validating the use of qRT-PCR as a method to quickly assess the effectiveness of vaccines and therapeutics being evaluated in the hamster SARS-CoV-2 model.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Hoagland and colleagues researchers assessed the lungs of SARS-CoV-2 infected hamsters for host immune gene regulation and found a prominent upregulation of IL-6, TNF, and IL-1beta 49 consistent with our PCR results. In another study single cell sequencing analysis revealed a prominent T cell response including upregulation of IFN-gamma and IL-2 50 , two markers we also noted to be highly expressed in the lungs. Importantly, the qRT-PCR analysis we reported in our present study is in agreement with these other studies thereby validating the use of qRT-PCR as a method to quickly assess the effectiveness of vaccines and therapeutics being evaluated in the hamster SARS-CoV-2 model.…”
Section: Discussionmentioning
confidence: 52%
“…These findings are important as these inflammatory markers have been shown to be predictors of severe disease via assessment of blood in humans [44][45][46][47][48] . More in-depth analysis of the host response to SARS-CoV-2 in the respiratory tissues of hamsters has been done using transcriptome sequencing analysis 49,50 . Hoagland and colleagues researchers assessed the lungs of SARS-CoV-2 infected hamsters for host immune gene regulation and found a prominent upregulation of IL-6, TNF, and IL-1beta 49 consistent with our PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…Hoagland and colleagues assessed the lungs of SARS-CoV-2 infected hamsters for host immune gene regulation and found a prominent upregulation of IL-6, TNF, and IL-1beta [43] consistent with our PCR results. In another study single cell sequencing analysis revealed a prominent T cell response including upregulation of IFN-gamma and IL-2 [44], two markers we also noted to be highly expressed in the lungs. Additionally, our analyses of the lungs revealed upregulation of T cell markers CD3, CD4 and CD8A.…”
Section: Fig 6 Sars-cov-2 Infection In Hamsters Leads To Increases In Inflammatory and Immune Mediator Related Genes In Select Extrapulmomentioning
confidence: 52%
“…These findings are important as these inflammatory markers have been shown to be predictors of severe disease via assessment of blood in humans [38][39][40][41][42]. More in-depth analysis of the host response to SARS-CoV-2 in the respiratory tissues of hamsters has been done using transcriptome sequencing analysis [43,44]. Hoagland and colleagues assessed the lungs of SARS-CoV-2 infected hamsters for host immune gene regulation and found a prominent upregulation of IL-6, TNF, and IL-1beta [43] consistent with our PCR results.…”
Section: Fig 6 Sars-cov-2 Infection In Hamsters Leads To Increases In Inflammatory and Immune Mediator Related Genes In Select Extrapulmomentioning
confidence: 99%
“…Although the analysis of blood was extremely instructive particularly when assessing systemic effects of COVID-19, the lung presents the primary site of infection for SARS-CoV-2 and investigating the local immune system response is key to understanding the pathology. Activated monocytes of the blood have been shown to infiltrate the lungs in patients with COVID-19 and in animal models of SARS-CoV-2 infection (160,161). In their seminal study, Liao et al characterized BALF from patients with varying severity of COVID-19 and healthy individuals using scRNA-seq and reported striking shifts in cellular composition with increased proportions of macrophages and neutrophils and lower proportions of DCs and T cells in samples from severe/critical COVID-19 compared to those from moderate disease and healthy individuals.…”
Section: High-resolution Single-cell Omics Characterization Of Monocytes and Macrophages In The Blood And Lungs Of Covid-19 Patientsmentioning
confidence: 99%